Standardization of an economical formulation for fishballs - Libunao, Lariza Q. (1989.)
Fishballs were prepared using Labahita fish (Acanthurus bleekeri, Linn.).
Thesis ( B.S. ) --SOTECH, University of the Philippines in the Visayas.
Keywords: Fishball; Labahita (Acanthurus bleekeri, Linn.)